Redesigning the Boundaries of Corruption in Government Procurement of Goods and Services - Andi Akbar Subari; Achmad Faisal; Suprapto Suprapto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Government procurement, particularly in Indonesia, remains highly susceptible to corruption due to systemic regulatory loopholes and excessive human discretion, often characterized by collusion and bid-rigging. This institutional vulnerability defines the traditional